Activated T-Follicular Helper 2 Cells Are Associated With Disease Activity in IgG4-Related Sclerosing Cholangitis and Pancreatitis. Issue 4 (April 2019) - Cargill, Tamsin; Makuch, Mateusz; Sadler, Ross; Lighaam, Laura C.; Peters, Rory; van Ham, Marieke; Klenerman, Paul; Bateman, Adrian; Rispens, Theo; Barnes, Eleanor; Culver, Emma L.
Abstract : OBJECTIVES: Immunoglobulin G4-related sclerosing cholangitis (IgG4-SC) and autoimmune pancreatitis (AIP) are characterized by an abundance of circulating and tissue IgG4-positive plasma cells. T-follicular helper (Tfh) cells are necessary for B-cell differentiation into plasma cells. We aimed at elucidating the presence and phenotype of Tfh cells and their relationship with disease activity in IgG4-SC/AIP. METHODS: Circulating Tfh-cell subsets were characterized by multiparametric flow cytometry in IgG4-SC/AIP (n = 18), disease controls with primary sclerosing cholangitis (n = 8), and healthy controls (HCs, n = 9). Tissue Tfh cells were characterized in IgG4-SC/AIP (n = 12) and disease control (n = 10) specimens. Activated PD1+ Tfh cells were cocultured with CD27+ memory B cells to assess their capacity to support B-cell differentiation. Disease activity was assessed using the IgG4–responder index and clinical parameters. RESULTS: Activated circulating PD-1+CXCR5+ Tfh cells were expanded in active vs inactive IgG4-SC/AIP, primary sclerosing cholangitis, and HC ( P < 0.01), with enhanced PD-1 expression on all Tfh-cell subsets (Tfh1, P = 0.003; Tfh2, P = 0.0006; Th17, P = 0.003). Expansion of CD27+CD38+CD19lo plasmablasts in active disease vs HC ( P = 0.01) correlated with the PD-1+ Tfh2 subset ( r = 0.69, P = 0.03). Increased IL-4 and IL-21 cytokine production from stimulated cells of IgG4-SC/AIP, important in IgG4 class switch and proliferation, correlated with PD-1+ Tfh2 ( r = 0.89, P = 0.02) and PD-1+ Tfh17 ( r = 0.83, P = 0.03) subsets. Coculture of PD1+ Tfh with CD27+ B cells induced higher IgG4 expression than with PD1− Tfh ( P = 0.008). PD-1+ Tfh2 cells were strongly associated with clinical markers of disease activity: sIgG4 ( r = 0.70, P = 0.002), sIgE ( r = 0.66, P = 0.006), and IgG4–responder index ( r = 0.60, P = 0.006). Activated CXCR5+ Tfh cells homed to lymphoid follicles in IgG4-SC/AIP tissues. CONCLUSIONS: Circulating and tissue-activated Tfh cells are expanded in IgG4-SC/AIP, correlate with disease activity, and can drive class switch and proliferation of IgG4-committed B cells. PD1+ Tfh2 cells may be a biomarker of active disease and a potential target for immunotherapy.